The Clavesin Family, Neuron-specific Lipid- and Clathrin-binding Sec14 Proteins Regulating Lysosomal Morphology - Katoh, Yohei (American Society for Biochemistry and Molecular Biology, 2009)
Clathrin-coated vesicles (CCVs) originating from the trans-Golgi network (TGN) provide a major transport pathway from the secretory system to endosomes/lysosomes. Herein we describe paralogous Sec14 domain-bearing proteins, clavesin 1/CRALBPL and clavesin 2, identified through a proteomic analysis of CCVs. Clavesins are enriched on CCVs and form a complex with clathrin heavy chain (CHC) and adaptor protein-1, major coat components of TGN-derived CCVs. The proteins co-localize with markers of endosomes and the TGN as well as with CHC and adaptor protein-1. A membrane mimic assay using the Sec14 domain of clavesin 1 reveals phosphatidylinositol 3,5-bisphosphate as a specific lipid partner. Phosphatidylinositol 3,5-bisphosphate is localized to late endosomes/lysosomes, and interestingly, isoform-specific knockdown of clavesins in neurons using lentiviral delivery of interfering RNA leads to enlargement of a lysosome-associated membrane protein 1-positive membrane compartment with no obvious influence on the CCV machinery at the TGN. Since clavesins are expressed exclusively in neurons, this new protein family appears to provide a unique neuron-specific regulation of late endosome/lysosome morphology.